EFFECT OF VARIABLE HELIX ANGLE OF END MILLING TOOL ON VIBRATION AND SURFACE ROUGHNESS OF SS-AISI 304 - Sonief, Achmad As’ad; Sasongko, Mega Nur; Widhiyanuriyawan, Denny Widhiyanuriyawan; Pratikto, Pratikto (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Vibration in milling processes adversely affects product quality, machining precision, tool lifespan, and operating costs. A common vibration type, chatter, arises from self-excitation influenced by cutting parameters. Chatter can be classified into regenerative and resonant types. To mitigate resonance, cutting tools with variable helix angles are employed, as their varying pitch angles generate distinct tooth-passing frequencies for each blade. This study investigates the impact of helix angles on cutting parameters during end milling and their effects on vibration amplitude and surface roughness of AISI 304 stainless steel. Experimental end milling trials were conducted with different helix angle tools and cutting parameter variations. The findings reveal that optimizing the helix angle significantly reduces vibration amplitude and enhances surface finish. Controlling helix angle proves crucial for achieving superior surface quality and stable operation in end milling processes of stainless steel materials.